Factitious prey and artificial diets: do they all have the potential to facilitate rearing of Typhlodromus bagdasarjani (Acari: Phytoseiidae)?. Issue 2 (3rd April 2018) - Riahi, Elham; Fathipour, Yaghoub; Talebi, Ali A.; Mehrabadi, Mohammad
ABSTRACT: The rearing possibility of Typhlodromus bagdasarjani (Phytoseiidae) on three factitious prey ( Ephestia kuehniella eggs, cysts of Artemia franciscana and Tyrophagus putrescentiae ), and nine artificial diets including a basic artificial diet (AD1) and the others (AD2–AD9) consisted of 80% AD1 enriched with different nutrients including maize pollen, haemolymph of Plusia gamma L., Ephestia eggs, Artemis cysts, Ephestia larvae, multivitamin syrup, bovine serum albumin and bull sperm, as well as a natural pollen diet (almond+ maize pollen) were investigated. None of the three factitious prey supported development of T. bagdasarjani beyond protonymphal stage. The highest GRR (gross reproductive rate), R 0 (net reproductive rate), r (intrinsic rate of increase) and λ (finite rate of increase) were obtained when the adults were reared on cysts of Artemia, immediately after their emergence. On pollen diet, all population growth parameters except T (mean generation time) were higher than artificial diets. The mites reared on AD6 and AD8 could not develop beyond deutonymphal stage. Although r was negative on both AD3 and AD5, its value on AD3 was higher. In conclusion, except pollen diet, none of diets tested is recommendable for mass rearing of this predator and utilizing on crop as alternative food.